Rho/MRTF-A-Induced Integrin Expression Regulates Angiogenesis in Differentiated Multipotent Mesenchymal Stem Cells - Rui Zhang; Nan Wang; Man Zhang; Li-Nan Zhang; Zhi-Xia Guo; Xue-Gang Luo; Hao Zhou; Hong-Peng He; Tong-Cun Zhang (Stem Cells International)
Mesenchymal stem cells (MSCs) are known to undergo endothelial differentiation in response to treatment with vascular endothelial growth factor (VEGF), but their angiogenic ability is poorly characterized. In the present study, we aimed to further investigate the role of Rho/MRTF-A in angiogenesis by MSCs and the effect of the Rho/MRTF-A pathway on the expression of integrins α1β1 and α5β1, which are known to mediate physiological and pathological angiogenesis. Our results showed that increased expression of α1, α5, and β1 was observed during angiogenesis of differentiated MSCs, and the Rho/MRTF-A signaling pathway was demonstrated to be involved in regulating the expression of integrins α1, α5, and β1. Luciferase reporter assay and ChIP assay determined that MRTF-A could bind to and transactivate the integrin α1 and α5 promoters. Treatment with the Rho inhibitor C3 transferase, the Rho-associated protein kinase (ROCK) inhibitor Y27632 or with shMRTF-A inhibited both the upregulation of α1, α5, and β1 as well as angiogenesis. Furthermore, in human umbilical vein endothelial cells (HUVECs), MRTF-A deletion led to marked reductions in cell migration and vessel network formation compared with the control. These data demonstrate that Rho/MRTF-A signaling is an important mediator that controls integrin gene expression during MSC-mediated angiogenic processes.